Improper lung volume-dose parameters are risk factors for acute fatal radiation pneumonitis among esophageal cancer patients receiving chemoradiotherapy: a case-control study - Jia, Ruinuo; Li, Liuyan; Liu, Xiaoyi; Zhang, Junqian; Li, Shuoguo; Wang, Ziqi; Li, Jingxia; Xu, Bingyi; Sheng, Manxi; Ni, Lei; Yang, Danni; Gao, Shegan (Frontiers in Oncology, 2025)
BackgroundDefinitive concurrent chemoradiotherapy (DCRT) is the standard treatment for locally advanced unresectable esophageal cancer (EC). However, acute fatal radiation pneumonitis (AFRP) is one of the most harmful complications and it is still controversial which factors pose a greater risk.AimThis case-control study aims to investigate the relationship between AFRP and lung volume-dose parameters in patients with esophageal cancer undergoing DCRT.MethodsCases are patients who died of AFRP after DCRT, whereas controls are patients who did not develop RP. Participants were enrolled using the International Classification of Diseases Codes Searching and then verified by medical record review. One-to-three propensity score matching was performed between EC patients undergoing DCRT who died from AFRP and those who did not develop radiation pneumonitis(RP). Prognostic factors were determined using univariate and multivariate analyses. The exposure factors were lung volume-dose parameters, including V5, V20, V30, and mean lung dose (MLD). Overall survival was compared between the two groups of patients before and after propensity score matching.Results17 cases were confirmed with AFRP among 568 EC patients were treated with DCRT between June 2008 and June 2013, and 51 cases with no RP matched by PSM method in the control group. The median V5 and MLD values in the case group were significantly higher than the control group: 88.39% versus 65.045% and 17.325 gray (Gy) versus 14.38 Gy, respectively. V5 > 60%, V20 > 25%, and MLD > 15 Gy were identified as independent risk factors for AFRP. V5 > 80% significantly increased the susceptibility to AFRP and predicted worse overall survival.ConclusionV5 > 60%, V20 > 25% and MLD > 15 Gy are key risk factors for AFRP in EC patients undergoing DCRT. Furthermore, V5 > 80% is a strong indicator of mortality risk.